Toxicity of dissolved and precipitated forms of barium to a freshwater alga (Chlorella sp. 12) and water flea (Ceriodaphnia dubia). (14th April 2018) - Golding, Lisa A.; McKnight, Kitty; Binet, Monique; Adams, Merrin; Apte, Simon C.
Abstract: Barium is present at elevated concentrations in oil and gas produced waters, and there is no international water quality guideline value to assess the potential risk of adverse effects to aquatic biota. Sulfate concentration largely controls the solubility of barium in aquatic systems, with insoluble barium sulfate (barite) assumed to be less bioavailable and less toxic than dissolved barium. We exposed aquatic biota to dissolved barium only and to a mixture of dissolved and precipitated barium. The chronic dissolved barium 48‐h growth rate inhibition effect concentrations, (EC10 and EC50) for the tropical freshwater alga Chlorella sp. 12 were 40 mg/L (27–54 mg/L 95% confidence limits [CL]), and 240 mg/L (200–280 mg/L 95% CL), respectively. The acute EC10 and EC50 values for 48‐h immobilization of the water flea ( Ceriodaphnia dubia ) by dissolved barium were 14 mg/L (13–15 mg/L 95% CL) and 17 mg/L (16–18 mg/L 95% CL), respectively. Chlorella sp. 12 was significantly more sensitive to precipitated barium than to dissolved barium, whereas the opposite seemed likely for C. dubia . Ceriodaphnia dubia was predicted to be chronically sensitive to dissolved barium at concentrations measured in produced waters and receiving waters, based on a predicted chronic EC10 of 1.7 mg/L derived from the acute EC50/10. Further chronic toxicity data that account for barium toxicity in dissolved and precipitated forms are required to derive a barium guideline for freshwater biota. Environ Toxicol Chem 2018;37:1632–1642. © 2018 SETAC Abstract : Sulfate controls the bioavailability of dissolved barium by precipitation of barium sulfate. However, barium sulfate precipitate can also be toxic to some aquatic biota and water quality guidelines need to account for dissolved and precipitated barium when assessing ecological impacts of oil and gas produced waters with high barium concentration.